The twisted throne ebook - Jensen, Danielle L. (The Bridge Kingdom, 2025)
In the fifth novel of the thrilling Bridge Kingdom series, a princess promised in marriage falls for the wrong brother, and their forbidden love threatens to destroy a fragile peace between kingdoms—from the New York Times bestselling author of A Fate Inked in Blood. A commander who bled to defend her people, Ahnna is haunted by two beliefs: The first is that she failed to protect Ithicana from invasion. And the second is that saving her homeland means leaving it behind forever. The Maridrinians left Ithicana in ruins and its people impoverished. So when the wealthy kingdom of Harendell claims Ahnna as a bride for its crown prince, she is prepared to do whatever it takes to gain influence as the future queen—and to control the gold that comes with the throne. Yet Ahnna swiftly discovers that beneath the beautiful surface of Harendell’s court is a dark underbelly of schemes, duplicity, and the pursuit of power. The only individual who holds himself above the politics is not her future husband but his infuriating half brother, James. And as she begins to question whether Harendell is the ally it claims to be, Ahnna finds herself drawn into a forbidden attraction to the wrong prince. As deadly plots tighten around her, Ahnna must decide whether saving her people will be achieved as a bride . . . or as a blade. Don’t miss any of Danielle L. Jensen's Bridge Kingdom series: THE BRIDGE KINGDOM • THE TRAITOR QUEEN • THE INADEQUATE HEIR • THE ENDLESS WAR • THE TWISTED THRONE (April 8, 2025)